Microclimate inside a tropical greenhouse equipped with evaporative cooling pads - Jamaludin, Diyana; Ahmad, Desa; Kamaruddin, Rezuwan; Jaafar, Hawa Z. E. (Universiti Putra Malaysia Press, 2014)
Tropical greenhouses require active evaporative cooling system such as pad-and-fan to ensure a suitable microclimate for crop production. Excess heat causes indoor temperature to become hotter than desired resulting in detrimental effects to crop growth and production. Solar radiation intensity and outside temperature affect temperature and relative humidity level inside a greenhouse, while wide gradients in temperature and relative humidity can cause problems related to crop growth and production uniformity. A 300 m2 greenhouse, equipped with evaporative pad and four exhaust fans at each end walls, was used in the study. Horizontal and vertical profiles of the temperature and relative humidity inside the greenhouse were investigated. Results showed that temperature increased from evaporative pad area to exhaust fans area in a horizontal plane, while relative humidity showed an inverse pattern from temperature. In the vertical plane, temperature increased, while relative humidity decreased from lower level to the upper level. ANOVA results showed that in overall, temperature and relative humidity inside the greenhouse were uniform as there was no significant difference at 95% confidence interval. Thus, it was concluded that greenhouse cooling system by evaporative pad and exhaust fans are suitable for application in a tropical country such as Malaysia.